Detection of Borrelia burgdorferi sensu stricto ospC alleles associated with human lyme borreliosis worldwide in non-human-biting tick Ixodes affinis and rodent hosts in Southeastern United States - Rudenko, Nataliia; Golovchenko, Maryna; Hönig, Václav; Mallátová, Nadja; Krbková, Lenka; Mikulásek, Peter; Fedorova, Natalia; Belfiore, Natalia M; Grubhoffer, Libor; Lane, Robert S; Oliver, James H (Applied and environmental microbiology, 2013)
Comparative analysis of ospC genes from 127 Borrelia burgdorferi sensu stricto strains collected in European and North American regions where Lyme disease is endemic and where it is not endemic revealed a close relatedness of geographically distinct populations. ospC alleles A, B, and L were detected on both continents in vectors and hosts, including humans. Six ospC alleles, A, B, L, Q, R, and V, were prevalent in Europe; 4 of them were detected in samples of human origin. Ten ospC alleles, A, B, D, E3, F, G, H, H3, I3, and M, were identified in the far-western United States. Four ospC alleles, B, G, H, and L, were abundant in the southeastern United States. Here we present the first expanded analysis of ospC alleles of B. burgdorferi strains from the southeastern United States with respect to their relatedness to strains from other North American and European localities. We demonstrate that ospC genotypes commonly associated with human Lyme disease in European and North American regions where the disease is endemic were detected in B. burgdorferi strains isolated from the non-human-biting tick Ixodes affinis and rodent hosts in the southeastern United States. We discovered that some ospC alleles previously known only from Europe are widely distributed in the southeastern United States, a finding that confirms the hypothesis of transoceanic migration of Borrelia species.
Keywords: alely; Borrelia burgdorferi; Ixodes; DNA bakterií; Antigens, Bacterial; North America; Humans; Rodentia; Severní Amerika; Sequence Analysis, DNA; Molecular Sequence Data; molekulární sekvence - údaje; klíště; antigeny bakteriální; Alleles; Genotype; lidé; zvířata; Europe; Bacterial Outer Membrane Proteins; genetická variace; sekvenční analýza DNA; Genetic Variation; DNA, Bacterial; proteiny vnější bakteriální membrány; hlodavci; genotyp; Animals; Evropa